2009
DOI: 10.1002/pd.2246
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fetal gender on first trimester nuchal translucency and maternal serum free β‐hCG and PAPP‐A MoM in normal and trisomy 21 pregnancies

Abstract: Correcting for fetal sex may be a worthwhile consideration. A cost-benefit analysis would be required to determine if it is feasible to introduce fetal gender assignment into the routine first trimester scan for the purpose of marker correction and whether this would have any significant impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
35
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 34 publications
4
35
1
1
Order By: Relevance
“…In addition, Timmerman et al [9] found that male fetuses with a large NT have a greater chance of a favorable outcome than females. Cowans et al [10] investigated the impact of correcting first trimester screening for fetal sex and found a detection rate of 88.8% in male fetuses compared to 91.2% in female fetuses (not statistically different). When the group adjusted for fetal sex, they found almost identical screen positive rates for a detection rate of 89.7% in male fetuses compared to 90.2% in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Timmerman et al [9] found that male fetuses with a large NT have a greater chance of a favorable outcome than females. Cowans et al [10] investigated the impact of correcting first trimester screening for fetal sex and found a detection rate of 88.8% in male fetuses compared to 91.2% in female fetuses (not statistically different). When the group adjusted for fetal sex, they found almost identical screen positive rates for a detection rate of 89.7% in male fetuses compared to 90.2% in females.…”
Section: Discussionmentioning
confidence: 99%
“…slightly increasing the detection rate for an unchanged false-positive rate). At present, it is recommended to adjust for smoking status [1] , and adjustment for fetal sex has been suggested to be worth considering [10] , but further studies are needed, including cost-benefit analyses. At present, more results are needed on the effect of obesity on NT before adjustments in screening can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Cowans et al 1 demonstrated the significant influence of fetal gender on values of nuchal translucency (delta NT) and level of free ß-hCG and PAPP-A in maternal serum during screening for chromosomal aneuploidies in the first trimester on a set of 56024 normal singleton pregnancies and in 722 pregnancies where the fetus had trisomy 21. Normal female fetuses had levels of nuchal translucency (delta NT) which were 9.4% lower, and maternal serum levels of free ß-hCG and PAPP-A were higher (by 14.7% and 6.3% respectively) compared to fetuses of male gender.…”
Section: Discussionmentioning
confidence: 99%
“…During screening for Down syndrome in the I. trimester of pregnancy, parameters with values dependent on fetal gender (fetal nuchal translucency measured by ultrasound, free β-hCG and PAPP-A levels in maternal serum) are evaluated when calculating "individual risk" of incidence of trisomy in the fetus [1][2][3][4] . Reliable non-invasive determination of fetal gender in the monitored time period could enable modification of normal values of these parameters based on fetal gender and make the algorithm for calculating "individual risk" more accurate.…”
Section: Introductionmentioning
confidence: 99%
“…Catalano et al (2012) reasoned that if the shifting distribution explanation were correct, indicators of fitness among male fetuses that survive to birth would fall below expected levels in conception cohorts that yield fewer than expected male infants (i.e., live male births). Based on previous research (Cole, 2010;Cowans et al, 2009;Dugoff et al, 2004;Goetzl et al, 2004;Jelliffe-Pawlowski et al, 2010;Kirkegaard et al, 2010;Sasaki et al, 2008;Yaron et al, 2001), they used the median male hCG score, measured in the second trimester of gestation, as an indicator of fitness among survivors of 71 monthly California conception cohorts. Because of autocorrelation in both series, they performed the analysis not on the raw hCG medians and sex ratios, but on residuals derived from a Box-Jenkins ARIMA model (Box et al, 1994).…”
mentioning
confidence: 99%